The fourth delay and community-driven solutions to reduce maternal mortality in rural Haiti: a community-based action research study - Tonya MacDonald; Suzanne Jackson; Marie-Carmèle Charles; Marius Periel; Marie-Vén; Alex Salomon; Éveillard Premilus (BMC, 2018)
Abstract Background In Haiti, the number of women dying in pregnancy, during childbirth and the weeks after giving birth remains unacceptably high. The objective of this research was to explore determinants of maternal mortality in rural Haiti through Community-Based Action Research (CBAR), guided by the delays that lead to maternal death. This paper focuses on socioecological determinants of maternal mortality from the perspectives of women of near-miss maternal experiences and community members, and their solutions to reduce maternal mortality in their community. Methods The study draws on five semi-structured Individual Interviews with women survivors of near-misses, and on four Focus Group Discussions with Community Leaders and with Traditional Birth Attendants. Data collection took place in July 2013. A Community Research Team within a resource-limited rural community in Haiti undertook the research. The methods and analysis process were guided by participatory research and CBAR. Results Participants identified three delays that lead to maternal death but also described a fourth delay with respect to community responsibility for maternal mortality. They included women being carried from the community to a healthcare facility as a special example of the fourth delay. Women survivors of near-miss maternal experiences and community leaders suggested solutions to reduce maternal death that centered on prevention and community infrastructure. Most of the strategies for action were related to the fourth delay and include: community mobilization by way of the formation of Neighbourhood Maternal Health/Well-being Committees, and community support through the provision/sharing of food for undernourished women, offering monetary support and establishment of a communication relay/transport system in times of crisis. Conclusions Finding sustainable ways to reduce maternal mortality requires a community-based/centred and community-driven comprehensive approach to maternal health/well-being. This includes engagement of community members that is dependent upon community knowledge, political will, mobilization, accountability and empowerment. An engaged/empowered community is one that is well placed to find ways that work in their community to reduce the fourth delay and in turn, maternal death. Potentially, community ownership of challenges and solutions can lead to more sustainable improvements in maternal health/well-being in Haiti.